Head and neck cancer surgery provision in England: A current analysis of contributing specialties caseloads. Issue 2 (February 2017) - Islam, Shofiq; Wates, Emma; Hayter, Jonathan P.
Abstract: To ascertain the current provision for surgery for head and neck cancer in England with respect to the operative caseloads of oral and maxillofacial, ear nose and throat (ENT) and plastic surgeons, we analysed data from the 2013 report of the National Head and Neck Audit (DAHNO). Clinicians were grouped by specialty of affiliation and assigned surgical caseloads were compared. There was a wide disparity in the extent of surgical activity between the specialties (p < 0.001), and the percentage of those active in head and neck oncology within each specialty similarly varied (p < 0.001).